2020
DOI: 10.3390/biom10111574
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Extract from Evening Primrose (Oenothera paradoxa) Inhibits Invasion Properties of Human Malignant Pleural Mesothelioma Cells

Abstract: Extracts from the defatted evening primrose (Oenothera paradoxa Hudziok) seeds are the source of a range of stable polyphenolic compounds, including ellagic acid, gallic acid, and catechin. Our studies evaluate, for the first time, the influence of evening primrose isopropanol extract (EPE) on malignant pleural mesothelioma (MPM) cells. MPM is rarely diagnosed, its high aggressiveness and frequently noted chemoresistance limit its treatment schemes and it is characterized by low prognostic features. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…The sensitivity of the cells to the drug was determined by the sulforhodamine B (SRB) assay described previously. 27 The results were calculated as a percentage of controls, and the IC 50 values were calculated with GraphPad Prism version 9.1 software (GraphPad Inc. San Diego, CA, USA) using a four-parameter nonlinear logistic regression. The potentiation factors (PF 50 values) at 50% growth inhibition were calculated from the ratio of the IC 50 for 5-FU divided by the 5-FU in the presence of the EPE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of the cells to the drug was determined by the sulforhodamine B (SRB) assay described previously. 27 The results were calculated as a percentage of controls, and the IC 50 values were calculated with GraphPad Prism version 9.1 software (GraphPad Inc. San Diego, CA, USA) using a four-parameter nonlinear logistic regression. The potentiation factors (PF 50 values) at 50% growth inhibition were calculated from the ratio of the IC 50 for 5-FU divided by the 5-FU in the presence of the EPE.…”
Section: Methodsmentioning
confidence: 99%
“…The evening primrose extract (EPE) was obtained and identified previously as described. 27 The EPE treatment was conducted within a growing medium supplemented with 5% FBS, and the EPE was added from fresh stock prepared solution in 20% EtOH (v/v in PBS) to cells to obtain a final EtOH concentration of 0.1% (v/v). The controls were subjected to 0.1% EtOH alone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by introducing the extract into the diet, these authors observed significantly reduced MPM tumor size in mouse xenografts, this affected the engraftment of the MPM cell line after C. scolymus extract treatment. Recently, we reported that a mixture of polyphenols obtained from Oenothera paradoxa seeds (evening primrose extract, EPE) revealed anti-invasive effects against MPM cells [ 79 ]. Evening primrose ( Oenothera paradoxa Hudziok), belonging to the Oenothera species, is used in Europe for edible oil production.…”
Section: Polyphenols In Malignant Pleural Mesothelioma Therapymentioning
confidence: 99%
“…On the other hand, Lewandowska et al have shown potential anti-metastatic properties of EPE against prostate and breast cancer types, namely by inhibiting the type IV collagenases (MMP-2 and MMP-9) responsible for cell migration, invasiveness, and metastasis [ 93 ]. Our latest study [ 79 ] revealed that EPE possesses the anti-metastatic specificity toward invasive MPM cancer cell types (MSTO-H211 and JU77). The extract, containing ellagic acid, gallic acid, (+)-catechin, PGG, and procyanidin B2, arrested invasive cells in the G2/M phase, negatively correlated with the migration of MPM cells, and inhibited the secretion of matrix metalloproteinase-7 (MMP-7), the latter factor directly engaged in the invasion process and metastasis.…”
Section: Polyphenols In Malignant Pleural Mesothelioma Therapymentioning
confidence: 99%